2001
DOI: 10.7863/jum.2001.20.8.915
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic features of ovarian cystadenofibromas: spectrum of findings.

Abstract: We have described the sonographic spectrum of findings of ovarian cystadenofibromas. The most frequent appearance was a unilocular cystic mass with gross papillary projections or solid nodules. In almost half of the tumors, vascularization could be detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 18 publications
1
53
0
4
Order By: Relevance
“…11 Except mucinous cystadenoma which was multiseptate almost all adnexal tumors were reported as unilocular anechoic cyst. 12,13 In our study, the cysts ranged from 5 cm to 36 cm, mostly unilocular and echo-free in the postmenopausal women and were reported as either functional cysts or benign tumors. Ekerhovd et al reported that the risk of malignancy associated with unilocular echo-free cysts was not higher than 1.6%.…”
Section: 4mentioning
confidence: 63%
“…11 Except mucinous cystadenoma which was multiseptate almost all adnexal tumors were reported as unilocular anechoic cyst. 12,13 In our study, the cysts ranged from 5 cm to 36 cm, mostly unilocular and echo-free in the postmenopausal women and were reported as either functional cysts or benign tumors. Ekerhovd et al reported that the risk of malignancy associated with unilocular echo-free cysts was not higher than 1.6%.…”
Section: 4mentioning
confidence: 63%
“…Both ovarian fibroma and struma ovarii are known to be difficult to classify, showing features suggestive of malignancy in many instances. 27,28 The case of cystadenofibroma was notable because for some authors, this kind of tumor may show typical findings, such as a thin-walled cyst with hyperechoic mural nodules 20 ; however, others have found this tumor very difficult to classify. 27 If we had also considered GI-RADS 4 as malignant, the sensitivity would have increased to 100%; the specificity would have dropped to 90%; and the positive likelihood ratio would have been lower (10.1; 95% confidence interval, 6.55-16.6).…”
Section: Discussionmentioning
confidence: 99%
“…Pattern recognition analysis was used for adnexal masses highly suggestive of given diseases such as endometrioma, 11 mature teratoma, 12 hydrosalpinx, 13 peritoneal cyst, 14 hemorrhagic cyst, 15 follicular cyst, 16 paraovarian cyst, 17 tubo-ovarian abscess, 18 simple cyst, 19 and cystadenofibroma. 20 After the morphologic evaluation was performed, the color Doppler gate was activated to identify vascular color signals within the tumor.…”
Section: Methodsmentioning
confidence: 99%
“…The false negative rate may be considered very low. The correlation of sonography features with histological diagnosis has been found to be high in some benign ovarian tumours such as endometrioma (Alcázar et al, 1997b), mature teratoma (Caspi et al, 1996), haemorrhagic cyst (Okai et al, 1994), simple cyst (Castillo et al, 2004), hydrosalpinx (Guerriero et al, 2000), peritoneal cyst (Guerriero et al, 2004) and cystadenofibroma (Alcázar et al, 2001a).…”
Section: Introductionmentioning
confidence: 99%